Analysis Of Variables Affecting Labor Absorption In Some Of The Convection Industry In Medan City - Firmansyah Tarigan (Inspirasi & Strategi (INSPIRAT): Jurnal Kebijakan Publik & Bisnis, 2021)
Problems welfare of residents in the city of Medan is still a problem that has not been resolved. One reason is that labor problems. The high rate of labor force growth is not matched by the growth of economic sectors such as industry. Industry convection in Medan has good prospects for growth in the future, because the clothing product is a basic requirement. The development of the industry will increase production capacity so as to create employment opportunities. Employment convection industry can not be separated from the internal and external factors that influence. This study to analyze the variables that affect employment in convection industry using data analysis techniques Miles and Huberman. The data obtained in this study originated from interviews, observation, documentation and study of literature from the Central Statistics Agency of Medan, the Department of Industry and Trade of the city of Medan. Based on this research, the variables that affect employment over the differentiated internal variables and external variables. Internal variables that affect employment is a strategic plan, the estimated production and sales, and new ventures. While external variables are technological, geographical, economic and labor market.